2015
DOI: 10.1016/j.annemergmed.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Necessity of Operational Flexibility in the Emergency Department

Abstract: Hospital-based emergency departments (ED), given their high cost and major role in allocating care resources,are at the center of the debate regarding how to maximize value in delivering healthcare in the United States. In order to operate effectively and create value, EDs must be flexible: the ability to rapidly adapt to the highly variable needs of patients. The concept of flexibility has not been well described in the ED literature. We introduce the concept,outline its potential benefits, and provide some i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 23 publications
2
17
0
2
Order By: Relevance
“…Researchers from disciplines as varied as Emergency Medicine, OM, Accounting and Strategy have recently examined ED operations from multiple perspectives. Ward et al (2015) address the tension between cost and flexibility in the ED. They draw on operations research and organizational theory to describe five forms of flexibility: physical, human resource, volume, behavioral, and conceptual.…”
Section: Academic Viewmentioning
confidence: 99%
“…Researchers from disciplines as varied as Emergency Medicine, OM, Accounting and Strategy have recently examined ED operations from multiple perspectives. Ward et al (2015) address the tension between cost and flexibility in the ED. They draw on operations research and organizational theory to describe five forms of flexibility: physical, human resource, volume, behavioral, and conceptual.…”
Section: Academic Viewmentioning
confidence: 99%
“…Multiple strategies hold promise. For example, activating EMS transportation prior to PCI center activation, 24 using the 911 system to transfer patients, 25 using operations research tools to enhance the operational flexibility of the ED, 26,27 enhancing regionalization efforts to reduce EMS response times, 28,29 standardizing the initial interaction with EMS (eg, patient staying on the stretcher), 24 enhancing hospital-EMS relationships, 22 and appropriate use of ground-based (rather than helicopter) EMS. 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…We found that there is an increased reliance upon part-time emergency physicians to provide clinical care. While human resource flexibility can be an important operational strategy to respond to the changing operational demands of the ED, 13 they receive little training, and may have less experience and familiarity with a facility’s operational policies, culture and practice. 14,15 Temporary ED staff have also been found to affect patient safety in the ED.…”
Section: Discussionmentioning
confidence: 99%